Effects of Nanosilica on the Properties of Ultrafine Cement–Fly Ash Composite Cement Materials - Kai Wang; Siyang Guo; Jiahui Ren; Pengyu Chen; Qihao Zhang (Nanomaterials)
The increasing incidence of structural failures, such as cracks and collapses, in rock masses within mines, tunnels, and other civil engineering environments has attracted considerable attention among scholars in recent years. Grouting serves as a principal solution to these issues. The Renlou Coal Mine in the Anhui Province is used as a case study to evaluate the effectiveness of nanosilica (NS) as an additive in ultrafine cement (UC), introducing a novel grouting material for practical applications. This study investigates the physical and microscopic properties of a UC–ultrafine fly ash (UFA) mixed slurry containing powdered NS. Slurries of pure UC, UFA-blended UC, and UFA-blended UC with NS were prepared, and their viscosity, water precipitation rate, and compressive strength were evaluated. Scanning electron microscopy and X-ray diffraction were used for microscopic analyses. The results showed that the addition of UFA and NS to the UC slurry induced a more compact structure with reduced porosity. It was found that the viscosity and 7 d and 28 d compressive strengths of the slurry containing 50% UFA decreased by 91%, 51%, and 29.2%, respectively, and the water separation rate increased by 306.5%. The decrease in early strength was more pronounced, and the UFA content should not exceed 25%. Compared with the slurry without NS, the viscosity and 7 d and 28 d compressive strength of the slurry containing 1.5% NS increased by 216%, 51.2%, and 37%, respectively, and the water separation rate decreased by 45%. Notably, when the NS content is 1.5%, the performance of cement slurry is improved the most, and more C-S-H gel is produced. Cement consumption costs could be lowered and slurry performance improved by replacing a part of the cement with UFA and NS. Finally, orthogonal tests were conducted to select the optimal proportions for cement grouting. The optimal blend was determined to be composed of 20% UFA and 1.5% NS, with a water–cement ratio of 0.6. The study’s results not only demonstrate that NS has a good effect on improving the performance of cement-based grouting materials but also provide new insights for the design and application of grouting support in underground engineering.